1998
DOI: 10.1046/j.1460-9592.1998.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric preoperative teaching: effects at induction and postoperatively

Abstract: In a randomized controlled trial at Duke University and University of North Carolina Hospitals, 143 two to six year old children undergoing elective ambulatory surgery were randomized into a control group who received routine preoperative teaching or an intervention group who received an interactive teaching book. Changes in behaviour were measured by a Vernon behavioural questionnaire preoperatively and again two weeks postoperatively. A Global Mood Score was assessed in the preoperative holding area, at arri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 20 publications
2
69
0
1
Order By: Relevance
“…Contudo, esta redução se limitou ao período que antecedeu a cirurgia, não apresentando efeito ansiolítico durante a separação dos pais ou durante a indução da anestesia. Com relação aos pais, tais programas podem reduzir os níveis de ansiedade 43,44 . Estudo conduzido por Kain e col. 45 mostrou que 95% dos pais gostariam de ter informações relacionadas à anestesia da criança, incluindo possíveis complicações.…”
Section: · Programas De Preparação Pré-operatóriosunclassified
See 1 more Smart Citation
“…Contudo, esta redução se limitou ao período que antecedeu a cirurgia, não apresentando efeito ansiolítico durante a separação dos pais ou durante a indução da anestesia. Com relação aos pais, tais programas podem reduzir os níveis de ansiedade 43,44 . Estudo conduzido por Kain e col. 45 mostrou que 95% dos pais gostariam de ter informações relacionadas à anestesia da criança, incluindo possíveis complicações.…”
Section: · Programas De Preparação Pré-operatóriosunclassified
“…However, this decrease was limited to the period before surgery without anxiolytic effect during parents' separation or anesthetic induction. As to parents, such programs may decrease anxiety 43,44 . A study by Kain et al 45 has shown that 95% of parents would like to be informed about their child's anesthesia, including potential complications.…”
Section: · Preoperative Preparation Programsmentioning
confidence: 99%
“…More than 40 years ago, Eckenhoff documented that pediatric psychological traumas may result from surgery and anesthesia. Six-month-old to six-year-old children are the most susceptible to presenting post-hospitalization behavioral disorders owing to their limited capacity to deal with abstract thinking 2,3 . Both surgeries in this study are considered elective surgeries, performed in a day hospital, that is, children come from the ambulatory, are operated on and discharged on the same day, except if there are complications.…”
Section: Introductionmentioning
confidence: 99%
“…Given that they are scheduled surgeries, there is a preoperative preparation. According to Margolis and Gimberg, ideally there should be a preoperative educational program containing a verbal description of the procedure together with the sensations to be experimented, associated with interactions between parents and children 3 . Directed to expanding the physician-patient relationship, we assessed the preparation provided to children and responsible people in the preoperative period, analyzing the psychological profile pre and postoperatively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation